2009
DOI: 10.1128/ec.00294-08
|View full text |Cite
|
Sign up to set email alerts
|

90-Kilodalton Heat Shock Protein, Hsp90, as a Target for Genotyping Cryptosporidium spp. Known To Infect Humans

Abstract: Small-subunit (SSU) rRNA-based methods have been commonly used in the differentiation of Cryptosporidium species or genotypes. In order to develop a new tool for confirming the genotypes of Cryptosporidium species, parts of the 90-kDa heat shock protein (Hsp90) genes of seven Cryptosporidium species and genotypes known to infect humans (C. hominis, C. parvum, C. meleagridis, C. canis, C. muris, C. suis, and the cervine genotype), together with one from cattle (C. andersoni), were sequenced and analyzed. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The reaction mixture consisted of 12.5 ll master mix, 200 nM from each primer, 0.2 units of Taq polymerase (as an activator) and 3 ll of the template DNA for the primary reaction and 1 ll for the secondary reaction in a total volume of 25 ll. The cycling conditions were carried out according to Feng et al (2009) with modification in the form of 50°C annealing temperature for the primary and the secondary reactions. The amplified products were visualized with 1.5 % agarose gel electrophoresis after ethidium bromide staining.…”
Section: Copro-npcr Assaysmentioning
confidence: 99%
“…The reaction mixture consisted of 12.5 ll master mix, 200 nM from each primer, 0.2 units of Taq polymerase (as an activator) and 3 ll of the template DNA for the primary reaction and 1 ll for the secondary reaction in a total volume of 25 ll. The cycling conditions were carried out according to Feng et al (2009) with modification in the form of 50°C annealing temperature for the primary and the secondary reactions. The amplified products were visualized with 1.5 % agarose gel electrophoresis after ethidium bromide staining.…”
Section: Copro-npcr Assaysmentioning
confidence: 99%
“…In Egypt, the predominant species in human are Cryptosporidium hominis and Cryptosporidium parvum with variance in the predominance of one more than the other in different study situations. [21][22][23] The Cryptosporidium prevalence is widely varied between countries and time. Reports showed that the Cryptosporidium prevalence is usually higher when molecular methods were used.…”
Section: Discussionmentioning
confidence: 99%
“…According to their homology, function and size, they can be divided into different families, e.g. It has also been implicated as molecular marker for identifying and differentiating parasite species and genotypes, such as Cryptosporidium and Ditylenchus (Feng et al 2009;Vovlas et al 2015). The molecular chaperone HSP90 is important in the folding and functioning of many proteins involved in cell survival, especially those participating in cell cycle regulation and signal transduction (Pearl and Prodromou, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been implicated as molecular marker for identifying and differentiating parasite species and genotypes, such as Cryptosporidium and Ditylenchus (Feng et al . 2009; Vovlas et al . 2015).…”
Section: Introductionmentioning
confidence: 99%